Microbial diversity of Mongolian traditional cheese based on high-throughput sequencing technology - LIU Min, LIN Jiawei, JIAO Yuwei, DU Haoyue (Zhongguo niangzao, 2024)
Using cheese produced by natural fermentation with Mongolian traditional wooden barrels in Inner Mongolia pastoral areas as raw materials, the microbial diversity of fermented curd and cheese samples at different stages of ripening was analyzed by Illumina MiSeq high-throughput sequencing technology. The results showed that the diversity of bacterial flora was the highest in fermented curd, the richness of bacterial flora and diversity of fungal flora were the highest in cheese at 10 d of ripening, and the diversity of fungal flora was the highest in cheese at 30 d of ripening. The dominant bacterial genera (average relative abundance>1%) in fermented curd and cheese during ripening were Lactococcus, Lactobacillus, Acetobacter, Raoultella, Gluconobacter and Streptococcus, and the dominant fungal genera were Geotrichum, Issatchenkia, Kluyveromyces, unclassified_f_Dipodascaceae, Pichia, Torulaspora and Dekkera. The results of principal coordinate analysis (PCoA) showed that the bacterial community structure was significantly different and the fungal community structure was more similar between fermented curd and cheese at 0 d of ripening, while the bacterial community structure was similar and the fungal community structure was significantly different between cheese samples at 10 d, 20 d and 30 d of ripening. In conclusion, the microorganisms in cheese were abundant during ripening, and the ripening process had a significant effect on microbial community structure.